Dasawisma Community Empowerment Program in Tappale Village, Libureng District, Bone Regency - Rukmana, Novayanti Sopia; Waru, Andi Tenri; Guntur, Muhammad; Johansyah, Oky Nur Pratiwi (Jurnal Aktor, 2024)
This study aims to determine the community empowerment in the Dasawisma Program in Tappale Village, Libureng Subdistrict, Bone Regency. This study uses a qualitative approach and produces descriptive data. Data collection is done throughobservation, interviews, and documentation techniques. The data obtained from the research are processed using an interactive analysis model, including data reduction, data presentation, and drawing and testing conclusions. The results of this study show that the Dasawisma program in Tappale Village covers the aspects of Cleanliness, Beauty, and Orderliness (K3). The empowerment of Tappale Village Dasawisma is carried out by the Village Government. The role and contribution of Tappale Village Dasawisma in preserving the environment have been felt, but not to the maximum extent. Based on the research conducted, it is found that according to the ACTORS empowerment theory, it has not been implementedeffectively, as analyzed through that theory. From the results of this research, it can be concluded that the implementation ofcommunity empowerment programs by Dasawisma in Tappale Village has not been successful. There are several obstacles faced by Tappale Village Dasawisma in empowering the community. In addition, there are also steps taken by Tappale VillageDasawisma to address these obstacles. The recommendations from this study are given based on the dimensions of eachACTORS theory.